PENGARUH TANGGUNG JAWAB MORAL DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN PELAPORAN WAJIB PAJAK BADAN (Studi pada Kantor Pelayanan Pajak Pratama Kendari) - Akib, Mulyati; Sari, Ika Maya; Asnia, Asnia (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
AbstractThe purpose of the research is knowing the effect of  moral responsibility and  quality  of  service  to  taxpayer  compliance  reporting agency  inTax Office Pratama Kendari. The Data used in this research are primary data and secondary data. The population in this research are all corporate taxpayer registered for 2015. The sampling method used is siple random sampling. Questionnaires which can be processed as many as 87 from 100 questionnaires distributed. Methods of data analysis in this research is multiple linear regression methods.         The results of this research indicate the moral responsibility and the quality of services positive and significant effect to taxpayer compliance reporting agency in Tax Office Pratama Kendari. The results for the coefficient of determination total Moralresponsibility and quality of service to taxpayer comliance reporting agency R2=0,483.This number can be used to see the contribution of the Moral responsibility and quality of service  to taxpayer compliance reporting egency. The figure has meaning that the contribution of Moral Responsibility and quality of service to taxpayer compliance reporting agency is 48,3%, while the remaining 51,7% was obtained from the contribution of other factors. Keywords: Moral Responsibility, Quality Of Service, Taxpayer Compliance Reporting Agency.